English Learning Outcome from Teaching-learning from Home: A Case Study on Cumilla District, Bangladesh - Bhuiyan, Md. Eunus Mia; Ikbal, Ahmed; Helal, Md. Shafiqul Alam; Hock, Oo Yu; Jahabar, Hameed (2021)
Man has been working outside the home from time immemorial. So far, the world has undergone pandemics, and Covid 19 is the most severe one. Covid 19 pandemic has emerged as a significant threat to the globe where people have to rethink their ways of life and living. Strict health rules like wearing the mask, maintaining social distance, avoiding mass gatherings, etc., have adverse effects on our social, cultural, traditional, and psychological arena. Like most countries, offline teaching-learning is an age-old tradition in Bangladesh. The education sector is the most affected sector due to pandemics, as all levels of the education sector of Bangladesh have been closed since March 17, 2020. This paper tries to show how teaching and learning can be done from staying at home. It also tries to determine whether this type of teaching and learning impacts the students' English learning and performance in this subject. This study employs a quantitative approach.